PERAN PENTING KOMUNIKASI ORANG TUA DALAM KASUS KEKERASAN SEKSUAL PADA ANAK - Sari, Novita; Purnama, Jelita Zahara (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
At that time there was a significant increase in acts of violence against children. In recent years, various incidents involving children, including sexual violence, have been widely reported in the mass media. This article explains the prevention of child sexual abuse by the family community. This research uses methods commonly used in qualitative approaches by conducting extensive interviews and observations to draw conclusions. The results of this study conclude that sexual violence against children can be prevented from an early age. How to give children an understanding of sex must be given in a gradual way. Communication about sex to children's education must start with respect so that the child does not laugh about the story and so that the child understands it better and that he does not ask about it. If we as parents want to give our children an example of how to use the words “sensitive” respectfully, we must be able to set a good example to our children, because children will imitate our behavior. By maintaining communication and creating more open communication with children, we as parents can also learn and get to know our children from an early age.